Coexistence Opportunities for Coal Seam Gas and Agribusiness. (29th December 2016) - Mehreen, Syeda U.; Underschultz, Jim R.
Summary: Australia's prospects to become a key energy exporter in the Asia‐Pacific region has driven rapid development and expansion of its coal seam gas (CSG) industry, particularly in regional Queensland, Australia. The vast majority of Australia's current CSG developments and reserves are situated in agriculture‐rich, cattle‐grazing regions; therefore, it is critical to identify symbiotic relationships between agri‐based industries and the CSG industry to achieve beneficial coexistence. The CSG industry has generated infrastructure such as gas and water pipelines, water storage and treatment facilities, transportation and electricity networks, and other CSG‐associated services (e.g., accommodation, education, and medical facilities), which have the potential to improve regional communities and facilitate economic growth. This article aims to investigate these coexistence opportunities, including the use of by‐products (mainly water produced during CSG extraction), infrastructure, and services generated from the CSG industry, which can provide value to the local industries. Focusing on the cattle value chain, the authors suggest an agri‐based industrial coexistence model that indicates material‐water flows and optimized utilization of infrastructure that not only promote coexistence between the agribusiness and CSG industries, but expand the cattle value‐chain productivity in rural Queensland. A water balance has been conducted around the suggested coexistence model with the aim of quantifying water flows, to indicate the supply versus demand scenario associated with CSG‐sourced water production. The results of the water balance indicate that CSG water supply has the potential to meet the requirements of agribusiness promoting industries.